A construção de uma UEPS para o ensino do efeito DOPPLER relativístico com elementos contextuais da cosmologia - Barbosa, Verônica Tavares (2023)
This dissertation discusses the results of the construction and implementation of a Potentially Significant Teaching Unit based on David Ausubel’s Theory of Meaningful Learning. Its intention is to classify itself as potentially significant material for teaching the relativistic Doppler effect with contextual elements of Cosmology to third-year high school students. Thinking about the problems inherent in the didactic transposition of this theme to basic education, we sought to investigate which pedagogical strategies could help students in the construction of meaningful learning. To this end, the UEPS was organized in accordance with the sequence of steps established by Moreira (2011), and incorporated into its structure are digital educational objects and the active Peer Instruction methodology. It is noteworthy that these strategies present themselves as alternatives to streamline expository classes and encourage active and collaborative participation by students. Regarding the characterization of the research, it is bibliographic in nature, with a qualitative and quantitative approach, and its objectives are exploratory-descriptive in nature. The UEPS results were analyzed in light of Bloom’s revised Taxonomy, revealing encouraging signs of acquisition, assimilation and construction of meaningful learning